Perspectives on the curriculum of teachers in a public school system and its relations with science education (Revista Contexto & Educação, 2026)
This study analyzes the perceptions of Science teachers in the municipal school system of Florianópolis regarding curriculum and pedagogical practice, considering the relationship between theoretical formulations and everyday school challenges. The investigation, with a qualitative approach, involved 36 participants who responded to questionnaires aimed at identifying their curricular conceptions. Results indicate that teachers have qualified educational backgrounds, with significant participation in graduate programs, predominantly in the field of Science Education. A prevalence of critical and post-critical conceptions of curriculum was observed, with emphasis on its political and social dimensions, as well as rejection of exclusively technical or traditional models. In the scope of Science Education, teachers demonstrate alignment with constructivist assumptions, valuing the problematization of prior knowledge and the social implications of scientific activity. Although work overload, intensification of labor, and structural limitations are verified, teachers report exercising autonomy to resignify curricular prescriptions according to school realities. The research evidences tensions between the guidelines of the National Common Curricular Base (BNCC) and teachers' conceptions, as well as the perception of different agents and instances of action in curricular construction. It is concluded that there is a need to recognize teacher protagonism in curricular re-elaboration processes and to ensure that educational policies incorporate the specificities of pedagogical work and the knowledge produced by teachers in the daily school routine.
Keywords: Curriculum; Science Education; Teacher Conceptions; Pedagogical Practice